Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Produktivitas Kerja PT Kamaltex - Puspitasari, Melisa; Wijayanto, Petrus (Universitas Proklamasi 45, 2024)
The resource that has the biggest role in the company's development is the workforce. Human resources are a factor that is difficult to predict because they are influenced by several things, both internal and external. Companies have goals, especially increasing productivity which is supported by the role of employees in optimizing profits. Companies can choose productive employees so work productivity will be maximized. However, if the workload is too large, employees also experience pressure, especially in limited circumstances and time. Even though there is a workload, factors that make employees experience satisfaction will also appear in their work to influence employee work productivity. This research aims to examine the effect of workload and job satisfaction on work productivity at PT Kamaltex which is located in Ngepon Village, Bergas District, Semarang Regency, Central Java. This research uses a quantitative method using secondary data in the form of data on the number of employees, salary data, and work productivity data at PT Kamaltex, and primary data in the form of data on the influence of workload and job satisfaction on work productivity. The results of this research show that workload and job satisfaction have a significant effect on work productivity.